Description of the larvae of Faula jaliscoensis (Delgado & Navarrete-Heredia) (Coleoptera: Scarabaeidae: Melolonthinae) from Nayarit, Mexico - Lugo-García, Gabriel A.; Cuate M., Víctor A.; Cortez-Isiordia, Kenedy A. (Zootaxa, 2018)
The larvae of Faula jaliscoensis (Delagado & Navarette-Heredia, 2004) (Coleoptera: Scarabaeidae: Melolonthinae: Macrodactylini) is described based in specimens collected in a sugarcane (Saccharum officinarum Linnaeus; Poaceae) field in Nayarit, Mexico. Diagnostic structures are illustrated and the differences between other described larvae of Faula Blanchard, 1850 are discussed. Faula was recently removed from synonymy with Ceraspis LePeletier & Serville, 1828 by Fuhrmann & Vaz-de-Mello (2017), with the following species occur in Mexico: Faula centralis (Sharp, 1877), F. jaliscoensis (Delagado & Navarette-Heredia, 2004), F. mexicana Harold, 1863, F. oaxacaensis (Delgado, 2001), and F. pilatei Harold, 1863 (Evans & Smith 2009). The objectives of this study are to describe the third instar of F. jaliscoensis and compare it with other described species of Faula in Mexico.